2019
DOI: 10.1097/pts.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record–Related Events in Medical Malpractice Claims

Abstract: Adverse events associated with health IT vulnerabilities can cause extensive harm and are encountered across the continuum of health care settings and sociotechnical factors. The recurring patterns provide valuable lessons that both practicing clinicians and health IT developers could use to reduce the risk of harm in the future. The likelihood of harm seems to relate more to a patient's particular situation than to any one class of error.This is an open-access article distributed under the terms of the Creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 24 publications
(20 reference statements)
1
44
0
Order By: Relevance
“…Medical errors have been recognized in both studies and lawsuits as an important cause of patient morbidity and mortality, with physicians and medical facilities held responsible . Indeed, unintended medical errors resulting from medical professionals using defective software devices have already begun to raise similar issues and concerns …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical errors have been recognized in both studies and lawsuits as an important cause of patient morbidity and mortality, with physicians and medical facilities held responsible . Indeed, unintended medical errors resulting from medical professionals using defective software devices have already begun to raise similar issues and concerns …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is currently very little published information available that describes the impact of health IT and other types of software on patient safety . Earlier studies have investigated general safety issues in only a small number of medical devices or in only a few types of software . The ECRI Institute, for example, publishes a list each year of its 10 most important “generic hazards—problems that result from the risks inherent to the use of certain types or combinations of medical technologies.” The institute's most recent list of health technology hazards includes at least 3 medical products (infusion pumps, ventilators, medical device software management) with safety risks tied, at least in part, to faulty software .…”
Section: Fda Medical Device Regulatory Categoriesmentioning
confidence: 99%
“…In addition, half of the largest U.S. EHR vendors are not meeting standards for usability testing, with two thirds conducting tests with fewer than the minimum 15 participants, as suggested by the National Institute of Standards and Technology, and one fifth conducting at least half of their tests using subjects with no clinical background (Ratwani et al, 2015). Substandard usability testing may contribute to serious, unintended consequences in the implementation of health information technologies (Graber, Siegal, Riah, Johnston, & Kenyon, 2015; Han et al, 2005; Nebeker, Hoffman, Weir, Bennett, & Hurdle, 2005). …”
mentioning
confidence: 99%
“…The Pennsylvania Patient Safety Authority [45] reported 889 medication errors attributed to HIT systems within six months. Graber et al [27] reported 248 malpractice claims attributed to HIT systems. Finally, a review of FDA data in 2011 [58] found 120 error reports related to HIT systems; 50.2% of these errors were related to the user interface, while 20.8% were related to calculation errors or other software bugs.…”
Section: Domain: Gui Applications In Healthcarementioning
confidence: 99%